Perspectiva de algunos actores sobre los modelos de educación para la salud subyacentes en programas de salud sexual y reproductiva dirigidos a adolescentes, Medellín 2004-2007 (2013)
ABSTRACT: To describe the perspective that some actors have on the health education models of the sexual and reproductive health programs aimed at the adolescents of the city of Medellin from 2004 to 2007. Methodology: grounded theory was used to perform a qualitative analysis of the data. Information was collected using sixteen semi-structured interviews. Six of these interviews were addressed to young members of the programs, and the remaining ten were intended for the technical operators. Additionally, the indicators proposed by Serrano were used in order to determine the type of health education model proposed for each intervention. Results and discussion: each of the studied sexual and reproductive health interventions showed a mixture of indicators that made it impossible to place any of these programs into a single health education model. Conclusions and recommendations: all the analyzed projects shared indicators from several models, which often pointed to a lack of coherence between the formalized model and its implementation.